University tutoring service in times of pandemic, a priority for students in the highlands of Puno - Yucra Mamani, Yudi Janeh (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2022)
Objective: This article aims to analyze the importance of university tutoring service for students at the Universidad Nacional del Altiplano de Puno (Peru), in the context of the global pandemic of covid-19. Originality/contribution: This documentation approach reveals the experience of the student tutoring service in a public university, after the implementation of the University Law No. 30220 five years ago and, for the first time, in a non-face-to-face education scenario, in addition, the socio-cultural relevance is analyzed. Method: Qualitative research was used in order to understand the perceptions, experiences and expectations of the students about the tutoring service. Strategies/information collection: Within the qualitative method, the semi-structured interview technique was applied to forty-four students from different professional training areas (engineering, biomedicine and social sciences). Conclusions: This study found that the university tutoring service is very important for students because it is a means through which they receive support, guidance, accompaniment, and orientation from their tutors.  For many students, tutoring becomes a fundamental and transversal need in their professional training. However, they demand that tutors accompany them from the first to the last semester, that they be professionals with a counseling and psychological orientation profile who, based on the student's culture, create tutoring strategies that take into account their Andean cosmovision (agricultural production procedures, commerce; family and community coexistence, beliefs and values; respect and appreciation of their natural resources) and help them overcome various problems. Likewise, the use of Google Meet (group sessions) and Facebook, WhatsApp or telephone (individual sessions) should be prioritized as resources for the achievement of welfare states, in the current context of pandemic.